The Sahara Emirate: Al Oaeda in the West, for the West? - Keenan, Jeremy H. (Social justice, 2010)
The article offers information and observations about the presence of the Al Qaeda terrorist organization in Sahel, Africa, and the role of the Western countries in the counterrrorism policy there. Topics include the use of terrorism in the region by the U.S. to arrange a military strategy, the counterterrorism efforts of the U.S. in the region, and the creation and structure of Al Qaeda in the Islamic Maghreb (AQIM), a region of Northern Africa. It is suggested that the U.S. has used propaganda and exaggerated the 2007 Djanet Airport terrorist attack to promote national interests and begin military intervention to create a self-fulfilling prophecy about terrorism in Africa.